Pengaruh Rakan Sebaya ke atas Tingkah Laku Hedonistik Belia IPT di Malaysia (Sains Humanika, 2013)
This study examined to what extent attachment with peers influence hedonistic behavior among youth in selected higher institutions in Malaysia. The ex post facto study involved 394 students from higher learning institutions in the Klang Valley. Data were collected through self administered questionnaires, adapted from Armsden and Greenberg (1987), and Zimbardo and Boyd (1999) and Schwartz (1992) to measure the attachment of peer towards hedonistic behavior. Descriptive and inferential analysis was conducted using SPSS and Amos (SEM). Results showed that the respondents (67.0%) have a moderate level of hedonistic behavior (M = 3.25, SD = 0.56). Further, the study found that the attachment with peer has a positive and significant relationship between hedonistic behavior and alienation dimension (Î² = .204, C.R = 2.972, Sig = .003). The results also showed the dimension of trust (Î² = - .034, C.R = - .551, Sig = .582) and communication dimensions (Î² = .281, C.R = 1.597, Sig = .751) had no significant effect towards hedonistic behavior. The study can provide an important and significant contribution towards a strategic planning to prevent the spread of hedonistic behavior and strengthen the youth character in IPT Malaysia.
Keywords: Hedonistic behavior; peer attachment; communication; alienation; trust